2018
DOI: 10.1002/jcp.27272
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA882 regulates leukemia inhibitory factor (LIF) by sponging miR‐15b in the endometrial epithelium cells of dairy goat

Abstract: Despite the fact that long noncoding RNAs (lncRNAs) play roles in almost all biological processes, little is known about their biological function in the endometrium during the formation of endometrial receptivity. In this study, a comprehensive analysis of lncRNAs in goat endometrial tissues on Day 5 (prereceptive endometrium, PE) and Day 15 (receptive endometrium, RE) of pregnancy was performed by using RNA-Seq. As a result, 668 differentially expressed lncRNAs (DELs) were found between the PE and RE. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…LIF is a kind of cytokine secreted by endometrial glands and plays an amazingly important role in embryo implantation during WOI (93,94). As a competing endogenous RNA for miR-15b, lncRNA882 regulates LIF by sponging miR-15b in endometrial epithelium cells of dairy goat (95). (There are 3 EVs-related references in this section.…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…LIF is a kind of cytokine secreted by endometrial glands and plays an amazingly important role in embryo implantation during WOI (93,94). As a competing endogenous RNA for miR-15b, lncRNA882 regulates LIF by sponging miR-15b in endometrial epithelium cells of dairy goat (95). (There are 3 EVs-related references in this section.…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Zhou et al showed that the lncRNA regulator of reprogramming could act as a ceRNA and “sponge” miR‐145 to inhibit its mediation of endometrial cancer stem cell differentiation. Besides this, Zhang et al elucidated that lncRNA882 regulated leukemia inhibitory factor by sponging miR‐15b. However, their samples were mainly collected from goat and only a few correlation tests were carried out …”
Section: Introductionmentioning
confidence: 99%
“…Besides this, Zhang et al elucidated that lncRNA882 regulated leukemia inhibitory factor by sponging miR‐15b. However, their samples were mainly collected from goat and only a few correlation tests were carried out …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of H19 was down-regulated in the endometrium of RIF (Zeng et al, 2017). LncRNA882 acted as a ceRNA for miR-15b and then indirectly regulated the level of LIF in goat endometrial epithelial cells (EECs) (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%